An investigation of Na-related defects in Cu2ZnSnSe4. Issue 27 (28th June 2017) - Han, Miaomiao; Zhang, Xiaoli; Zeng, Zhi
Abstract : In this work, we have investigated the Na-related defect properties and migration mechanisms of Na in Cu2 ZnSnSe4 . Abstract : Using hybrid density functional theory, here, we have investigated the electronic, defect and migration properties of Na-related defects in the earth-abundant solar cell absorber material Cu2 ZnSnSe4 (CZTSe). We find that among all the Na-related defects, NaZn acts the same way as VCu and CuZn ; it is an acceptor and contributes to the p-type conductivity. NaSn is a deep level defect, but it is energetically unfavorable and can be suppressed by the growth conditions. Besides, through migration energy analysis, we prove that Na can easily move in CZTSe through interstitial Na and Cu vacancy mediated mechanisms.